1973
DOI: 10.1063/1.1662232
|View full text |Cite
|
Sign up to set email alerts
|

The detection of fatigue damage by exoelectron emission

Abstract: Plastic deformation of metal enhances the photoelectron emission producing so-called exoelectrons In our experiments the metal surface is scanned by a small spot of ultraviolet light and the electron emission is recorded as a function of position of the light spot. Results for aluminum and steel demonstrate that fatigue deformation produces exoelectron emission after less than 1% of the fatigue life. The regions of emission are very localized; some are beyond the resolution of the apparatus (15 μm). The locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Determine parameters S •• and τ of the obtained kinetic curve I(t) using Eqs. (14) and (16), respectively.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Determine parameters S •• and τ of the obtained kinetic curve I(t) using Eqs. (14) and (16), respectively.…”
Section: Papermentioning
confidence: 99%
“…The method of optically stimulated electron emission (OSEE) [12,13] is used increasingly in studies of photosensitive defects and properties of the surface layer of materials. The theory and hardware of the OSEE method have been well developed and it has shown itself useful in studies of fatigue failures and plastic deformations in metals [11,14], color centers in surface layers of oxide crystals, and glasses [15]. However, some methodological difficulties limit the development and wider use of OSEE in studies of point defects on the surface of dielectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…Photostimulated electron emission has been employed to monitor surface oxide fracture [6] and slip band formation during fatigue and deformation [7][8][9][10]. For instance, Baxter reported a linear increase of PSE with strain at strains less than 0.10 in aluminum and copper.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,[28][29][30][31][32][33][34][35][36][37][38][39][40] Electron microscopy, autoradiographic stripping, 29 and photoemission spectroscopy 17,37 showed that these signals were closely associated with the formation of slip lines and bands on deformed surfaces. 17,18,[28][29][30][31][32][33][34][35][36][37][38][39][40] Electron microscopy, autoradiographic stripping, 29 and photoemission spectroscopy 17,37 showed that these signals were closely associated with the formation of slip lines and bands on deformed surfaces.…”
Section: Discussionmentioning
confidence: 99%